2021
DOI: 10.3390/nu13020495
|View full text |Cite
|
Sign up to set email alerts
|

A Korean-Style Balanced Diet Has a Potential Connection with Ruminococcaceae Enterotype and Reduction of Metabolic Syndrome Incidence in Korean Adults

Abstract: Metabolic syndrome is associated with usual dietary patterns that may be involved in enterotypes. We aimed to understand the potential relationship of enterotypes and dietary patterns to influence metabolic syndrome in the Koreans. Using the Korea National Health and Nutrition Examination Survey (KNHANES)-VI in 2014, metabolic parameters were also analyzed among the dietary patterns classified by principal component analysis in Korean adults. The fecal microbiota data of 1199 Korean adults collected in 2014 we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 55 publications
3
39
1
1
Order By: Relevance
“…Dietary patterns have been reported to influence obesity risk [39][40][41][42]. A plant-based diet was inversely associated with the obesity risk, whereas a Western-style diet had a positive association in the present study.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Dietary patterns have been reported to influence obesity risk [39][40][41][42]. A plant-based diet was inversely associated with the obesity risk, whereas a Western-style diet had a positive association in the present study.…”
Section: Discussioncontrasting
confidence: 49%
“…These results suggest that the reduced obesity risk may be related to the gut microbiome because a high plant-based diet had a higher dietary fiber intake, but a Western diet had a lower fiber intake. Previous studies [40][41][42] reported that the participants with vegetarian-type diets have more of the Prevotella enterotype in the Western countries, whereas among Koreans, those with a rice-based diet have a higher level of Prevotella. Therefore, a plant-based diet may be intermediate between a rice-based diet and a balanced Korean diet.…”
Section: Discussionmentioning
confidence: 95%
“…Korean balanced diet has some beneficial effects on metabolic syndrome, cardiovascular disease, possibly, and type 2 diabetes. In the present study, food intake was estimated with 3-day food records, indicating that the participants in the AGM and placebo groups mainly had a Korean balanced diet including rice, soup, fermented cabbage and soybeans, beans, fish, cooked vegetables and fruits, and the persons who consume a Korean balanced diet belong to Ruminococus enterotype [ 53 ]. There was no difference in the intake of individual foods.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial DNA were extracted from individual feces samples using a Power Water DNA Isolation Kit (MoBio, Carlsbad, CA, USA). DNA libraries were prepared using the GS-FLX Plus emPCR Kit (454 Life Sciences, Branford, CT, USA) and amplified using 16S universal primers (V3 region) in the FastStart High Fidelity PCR System (Roche, Basel, Switzerland), as previously described [ 7 ]. Sequencing of bacterial DNA in feces was performed by Macrogen Ltd (Seoul) using a Genome Sequencer FLX Plus (454 Life Sciences), as previously reported [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…Asians have lower insulin secretion capacities and β-cell masses than Caucasians and thus are more susceptible to T2DM [ 3 ]. These ethnic differences are related to genetic and gut microbiome differences [ 5 , 6 , 7 ]. In concert with improvements in economic status, Asians now adopt more sedentary lifestyles and eat more refined and fatty foods.…”
Section: Introductionmentioning
confidence: 99%